2019
DOI: 10.3389/fonc.2019.00391
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Particle Irradiation With the Hedgehog Inhibitor GANT61 Differently Modulates the Radiosensitivity and Migration of Cancer Cells Compared to X-Ray Irradiation

Abstract: Due to the advantages of charged particles compared to conventional radiotherapy, a vast increase is noted in the use of particle therapy in the clinic. These advantages include an improved dose deposition and increased biological effectiveness. Metastasis is still an important cause of mortality in cancer patients and evidence has shown that conventional radiotherapy can increase the formation of metastasizing cells. An important pathway involved in the process of metastasis is the Hedgehog (Hh) signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…To the best of our knowledge only two studies looked into the effect of particles on the Hh pathway. Recently, we showed that carbon ions were more effective in inducing significant alterations in the Hh pathway than photons (102) and that carbon ions in combination with a Hh inhibitor was more efficient in decreasing migration of MCF-7 breast cancer cells than X-ray irradiation (170).…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge only two studies looked into the effect of particles on the Hh pathway. Recently, we showed that carbon ions were more effective in inducing significant alterations in the Hh pathway than photons (102) and that carbon ions in combination with a Hh inhibitor was more efficient in decreasing migration of MCF-7 breast cancer cells than X-ray irradiation (170).…”
Section: Hedgehog Pathwaymentioning
confidence: 99%
“…Therefore, particle therapy in combination with Hh inhibitors could offer an additional benefit for these patients due to the superior targeting. In a recent study, inhibition of Hh signaling radiosensitized medulloblastoma cells to both proton and carbon irradiation (102).…”
Section: Inhibition Of Hedgehog Pathwaymentioning
confidence: 99%
“…A recent study reports that GANT61 is able to sensitize DAOY cells to particle radiation (i.e. protons and carbon ions), but not to conventional X-rays [149] highlighting that the combination of GANT61 with particle radiation could offer a benefit for the treatment of specific cancer types.…”
Section: Direct Inhibition Of Glis Transcriptional Activity 2421 mentioning
confidence: 99%
“…For example, CIRT may limit HIF‐1a stabilization, MMP‐2 expression, and/or activation of the main epithelial–mesenchymal transition (EMT) signaling pathways that can trigger migration/invasion under normoxic and hypoxic conditions prevalent in radioresistant tumors relative to x rays . Compared to x rays or protons, carbon ions have also been reported to be more effective in decreasing cell survival and migration in prostate and pediatric medulloblastoma cells, as well as inducing more significant alteration in Hedgehog genes, another metastasis signaling pathway . Future biologically optimized treatment planning may be critical to the successful implementation of these advantages .…”
Section: Opening Statementsmentioning
confidence: 99%